Nanomaterials for Advanced Biological Applications - Rahmandoust, Moones; Ayatollahi, Majid R.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents an overview of the ways in which the latest experimental and theoretical nanotechnologies are serving the fields of biotechnology, medicine, and biomaterials. They not only enhance the efficiency of common therapeutics and lower their risks, but thanks to their specific properties, they also provide new capabilities. Nano-scale measurement techniques, such as nano-indentation and nano-scratch methods, could potentially be used to characterize the physical and mechanical properties of both natural tissues and synthetic biomaterials in terms of strength and durability.
Introduction -- Nanotherapeutics -- Drug delivery system -- Luminescent quantum dots Spectroscopy techniques -- Nanoparticles for bioimaging -- Microfluidic devices -- Single molecule biosensing -- Molecular rotors -- Lab-on-chip.
Keywords: Biomedical engineering; Biomaterials; Nanochemistry; Nanoscience; Nanotechnology; Microtechnology; Microelectromechanical systems; Biomedical Engineering and Bioengineering; Biomaterials; Nanochemistry; Nanophysics; Nanotechnology; Microsystems and MEMS